The Impact of Land Artificialization on Vegetation Cover and Land Surface Temperature (LST) in The Greater Constantine - Kahoul Meriem; Mazouz Toufik; Kallab Debih Naouel (Journal of Multidisciplinary Applied Natural Science, 2026)
Since the mid-1990s, Greater Constantine has undergone rapid and fragmented urbanization driven by population growth and resettlement policies, causing land artificialization, vegetation loss, and microclimatic changes. This study investigates the relationships between urban growth, vegetation cover, and land surface temperature (LST) from 1995 to 2024 using multi-temporal Landsat imagery processed in Google Earth Engine. The methodology combines supervised land-cover classification using the CART algorithm and the Dynamic World dataset, extraction of vegetation and thermal indices (NDVI and LST.), Normality test was evaluated using the Kolmogorov–Smirnov test with Lilliefors correction, revealing non-normal distributions for all variables (p ≤ 0.001). Therefore, Spearman’s rank correlation was used as the primary measure, while Pearson’s correlation was included for comparison. The results show a +68.21% increase in built-up areas and a −30.05% decrease in vegetated surfaces over the study period. Land surface temperature increased from 21.4 °C in 1995 to 32.6 °C in 2024, with a peak in 2015 (35.51 °C), partly attributable to El Niño event of that year. Statistical analysis indicates a weak inverse relationship between NDVI and LST (Spearman R² = 0.102–0.215) and a positive relationship between NDBI and LST (Spearman R² = 0.269–0.349). confirming that surface artificialization exerts a stronger influence on urban warming than vegetation loss alone. Nevertheless, the moderate explanatory power of both indices indicates that additional factors, including urban morphology, topography, and regional climatic forcing, contribute to spatial temperature variability. A key methodological limitation is the use of two distinct classification approaches (CART for 1995–2005; Dynamic World for 2015–2024), which introduces inter-temporal comparability uncertainty that should be considered when interpreting changes. These findings emphasize the need for nature-based urban planning, including green corridors, tree canopy targets, and permeable surface regulations, to reduce surface warming and strengthen climate resilience in rapidly urbanizing Mediterranean cities.